2011
DOI: 10.1152/ajpgi.00150.2011
|View full text |Cite
|
Sign up to set email alerts
|

Altered lipid metabolism in Hfe-knockout mice promotes severe NAFLD and early fibrosis

Abstract: Tan TC, Crawford DH, Jaskowski LA, Murphy TM, Heritage ML, Subramaniam VN, Clouston AD, Anderson GJ, Fletcher LM. Altered lipid metabolism in Hfe-knockout mice promotes severe NAFLD and early fibrosis. Am J Physiol Gastrointest Liver Physiol 301: G865-G876, 2011. First published August 4, 2011; doi:10.1152/ajpgi.00150.2011.-The HFE protein plays a crucial role in the control of cellular iron homeostasis. Steatosis is commonly observed in HFE-related iron-overload disorders, and current evidence suggests a caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 43 publications
9
49
1
Order By: Relevance
“…Serum alanine aminotransferase (ALT), iron, cholesterol, and triglyceride measurements were performed as previously described. 19 Quantitative Real-Time PCR Analysis Total cellular RNA was isolated from hepatic tissue using the TRIzol reagent (Invitrogen, Melbourne, Australia) according to the manufacturer's instructions. Reverse transcription and quantitative RT-PCR (Applied Biosystems, Brisbane, Australia) were performed as previously described.…”
Section: Serum Biochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Serum alanine aminotransferase (ALT), iron, cholesterol, and triglyceride measurements were performed as previously described. 19 Quantitative Real-Time PCR Analysis Total cellular RNA was isolated from hepatic tissue using the TRIzol reagent (Invitrogen, Melbourne, Australia) according to the manufacturer's instructions. Reverse transcription and quantitative RT-PCR (Applied Biosystems, Brisbane, Australia) were performed as previously described.…”
Section: Serum Biochemistrymentioning
confidence: 99%
“…Reverse transcription and quantitative RT-PCR (Applied Biosystems, Brisbane, Australia) were performed as previously described. 19 The primer sequences used for the experiments are outlined in Supplementary Table S3. Gene expression was normalized to the internal standard basic transcription factor 3 (Btf3).…”
Section: Serum Biochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has observed similar evidence in Hfe -/-mice fed a high calorie diet (HCD). This study showed a significant increase in serum alanine amino transferase (ALT), a marker of liver injury, and increased hepatic inflammatory and fibrogenic gene expression in Hfe -/-mice fed a HCD which develop steatohepatitis and early fibrosis (10). The mechanisms underlying the development of more severe injury are however not fully understood and require further investigation.…”
Section: General Introductionmentioning
confidence: 93%